Papilledema. An updated approach. - Yaney González Yglesias; Pilar Chang Chao; Inés Zamora Galindo; Eduardo Hernández Peña (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
The term papilledema refers to the edema that appears in the optic papilla after intracranial hypertension. Some of its most frequent causes are intracranial lesions, hydrocephaly, thrombosis venous sinus and meningitis. The increase of intracranial tension is related with the results of the eye´s fundus examination, which are classified differently: incipient, established, chronic, and atrophic, depending on its severity or development. It is indispensable to carry out imaging tests before performing lumbar puncture. This article is an approach to the diagnosis and treatment of this gnoseological entity.